Determination of the Cracking Resistance of Hot-Mix Asphalt Prepared with Capsules Containing Waste Oil - Ozdemir, Ahmet Munir; Yalcin, Erkut; Yilmaz, Mehmet; Kok, B. Vural; Hernandez, Alvaro Garcia (Asce-Amer Soc Civil Engineers, 2024)
Hot-mix asphalts are composite materials with self-healing properties: cracks in pavements constructed with these asphalts can close without external help. However, this self-healing process is slow, and cracks may reopen quickly. To increase the self-healing ratio and accelerate the healing process, capsules containing two different types of waste oil (vegetable and mineral oil) were added to the mixture at four different proportions (0.25%, 0.50%, 0.75%, and 1.00% by weight of the mixture). This research evaluated the effect of the capsule addition on the strength of the mixture against cracking. Experiments using samples with added semicircular capsules and samples containing no added capsules were carried out according to the linear elastic and elastic-plastic fracture mechanical principles. The self-healing properties of the hot-mix asphalt were determined. The results showed that the highest strength against cracking at low temperature was found in the sample with a proportion of 0.25% capsules of both types (waste vegetable and mineral oil). In addition, the oil released from the capsules increased the self-healing properties of the hot-mix asphalt. Samples fractured at 0 degrees C had better healing than the samples fractured at 25 degrees C.
Keywords: Self-healing; Asphalt mixture; Calcium alginate capsules; Waste vegetable oil; Waste mineral oil